Cyano Modification on Uridine Decreases Base‐Pairing Stability and Specificity through Neighboring Disruption in RNA Duplex. (19th November 2018) - Mao, Song; Ranganathan, Srivathsan V.; Tsai, Hsu‐Chun; Haruehanroengra, Phensinee; Shen, Fusheng; Valsangkar, Vibhav A.; Han, Bo; Hassan, Abdalla E. A.; Chen, Alan; Sheng, Jia
Abstract: 5‐Cyanomethyluridine (cnm 5 U) and 5‐cyanouridine (cn 5 U), the two uridine analogues, were synthesized and incorporated into RNA oligonucleotides. Base‐pairing stability and specificity studies in RNA duplexes indicated that cnm 5 U slightly decreased the stability of the duplex but retained the base‐pairing preference. In contrast, cn 5 U dramatically decreased both base‐pairing stability and specificity between U:A and other noncanonical U:G, U:U, and U:C pairs. In addition, the cn 5 U:G pair was found to be stronger than the cn 5 U:A pair and the other mismatched pairs in the context of a RNA duplex; this implied that cn 5 U might slightly prefer to recognize G over A. Our mechanistic studies by molecular simulations showed that the cn 5 U modification did not directly affect the base pairing of the parent nucleotide; instead, it weakened the neighboring base pair in the 5′ side of the modification in the RNA duplexes. Consistent with the simulation data, replacing the Watson–Crick A:U pair to a mismatched C:U pair in the 5′‐neighboring site did not affect the overall stability of the duplex. Our work reveals the significance of the electron‐withdrawing cyano group in natural tRNA systems and provides two novel building blocks for constructing RNA‐based therapeutics. Abstract : Pair up ! The synthesis and base‐pairing studies of naturally occurring 5‐cyano‐modified uridines in RNA are presented. Molecular simulations show that the cn 5 U modification does not directly affect the base pairing of the parent nucleotide; instead, it weakens the neighboring base pair in the 5′ side of the modification in the RNA duplexes.